Peran Literasi Keagamaan Dengan Sikap Moderasi Beragama Pada Mahasiswa Universitas Muhammadiyah Mamuju - Syahril Hatta; Rachmat; Nurfadhilah (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2026)
This study aims to deeply understand how religious literacy is interpreted and its role in shaping religious moderation among students at Muhammadiyah University of Mamuju. The study used a descriptive qualitative approach, with active students who had taken Islamic Religious Education courses and were involved in religious activities and campus organizations as subjects. Data collection was conducted through in-depth interviews, observation, and documentation. Indicators of religious literacy include understanding aspects of faith, worship, and morals, while indicators of religious moderation include attitudes of tolerance, inclusiveness, and the ability to reject extremism and radicalism. The results indicate that students' religious literacy is generally in the good category. In terms of faith, students have an adequate basic understanding, although there is still variation in contextual interpretations. In terms of worship, students understand the procedures for performing worship well, but consistency and internalization of values vary. Meanwhile, in terms of morals, students have a good understanding of Islamic moral values, although their implementation is not yet fully consistent. On the other hand, students' religious moderation attitudes are also considered good, characterized by tolerance of differences, inclusiveness in social interactions, and critical thinking skills in rejecting extremism and radicalism. However, there is still variation in the level of internalization of these attitudes, influenced by social environment, academic experience, and exposure to digital media. This study concludes that religious literacy plays a crucial role in shaping students' religious moderation attitudes, necessitating reinforcement through dialogical, contextual, and ongoing learning.